Geochemisty of Radioactive Waste Disposal - Bird, G. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1979)
Abstract Safe, permanent disposal of radioactive wastes requires isolation of a number of elements including Se, Te, I, Sr, Cs, Pd, U, Np, Pu and Cm from the environment for a long period of time. The aquatic chemistry of these elements ranges from simple anionic (I", 10"3) and cationic (Cs+, Sr++) forms to multivalent hydrolyzed complexes which can be anionic or cationic (Pu(OH)^,Pu(OH)t Pu02(C03)(OH)', Pu02C1+ etc.) depending on the chemical environment. The parameters which can affect repository safety are rate of access and compostion of groundwater, stability of the waste container, stability of the waste form, rock-water-waste interactions, and dilution and dispersion as the waste moves away from the repository site. Our overall research program on radioactive waste disposal includes corrosion studies of containment systems, hydrothermal stability of various waste forms, and geochemical behaviour of various nuclides including solubilities, redox equilibria, hydrolysis, colloid formation and transport, ion exchange equilibria and adsorption on mineral surfaces, and irreversible precipitation reactions. This paper discusses the geochemistry of I, Se, Te, Cs, Sr and the actinide elements and potential mechanisms by which the mobility could be retarded if necessary.